Urban displacement and placemaking in public space for wellbeing: a systematic review of global literature - te Lintelo, Dolf J. H.; Ip, Morgan Alexander; Lappi, Tiina Riitta; Lakshman; Rajith Weligamage Don; Hemmersam, Peter; Dar, Anandini; Tervonen, Miika (SAGE PUBLICATIONS LTD, 2025)
Cities and towns are critical geographies of refuge for a globally unprecedented number of forcibly displaced people. Yet urban processes also expose these groups and the local urban poor to recurrent displacements. While such experiences are shared, studies often treat these populations as distinct. Drawing on Yiftachel's notion of displaceability, this paper systematically reviews and synthesizes a global literature on diversely displaced people's placemaking in urban public space. Observing a significant analytical gap regarding cities of the so-called global South, the paper identifies a heuristic, and key analytical dimensions shaping divergent access and uses of public space by variously displaced populations. These concern: temporal patterns; powerful meta-narratives of people and place; and complex multi-scalar and multi-actor configurations of regulatory regimes governing public space. Simultaneously, acquisition and deployment of urban knowledge and a practice of (in)visibility enable differentially displaced populations' everyday claims to public space for wellbeing.